University Mathematics for Engineers: Towards Optimum Compromise between Interactive and Traditional Approaches - E. A. Beliauskene; O. N. Imas; S. V. Kriviakov; E. V. Tsareva (Высшее образование в России)
The article examines two ways to achieve mastery of undergraduate mathematics: face-to- face and digital learning formats. The authors have developed and tested a unique interactive computer-based learning software – few local programs to practice math online, offline or to be installed into an e-course. We focus on different standard problems, such as, finding determinants, solving differential equations, integration by parts, etc. The aim of this study was to investigate what kinds of the activities lead to good learning outcomes. To date, much of the previous research has suggested that students get the benefits of e-learning and b-learning. Yet, there is a general lack of research on outcomes compares the different ways in which students gain knowledge. The results show that the interactive math simulator is one of the effective tools for developing skills to solve standard problems of higher mathematics. There are, however, some math problems to be learn traditionally, with textbook and chalkboard.